Precipitation trends and their relationship with El Niño Oceanic Index. The case of the Mixteca Region, Mexico - P. F. Martínez-Austria; D. Díaz-Jiménez (Ingeniería del Agua)
The occurrence of droughts is a permanent concern in arid and semi-arid zones, especially for socially vulnerable ones such as the Mixteca Region in Mexico, a condition that can be aggravated as climate change scenarios predicts. The general circulation models do not allow forecasting precipitation conditions at regional scales, so it is necessary to study local climate behavior and trends. Determining the relationship between local climate and large-scale phenomena, such as El Niño / La Niña events, is relevant to set up prevention measures. This article analyzes the precipitation trends in the Mixteca Region of Mexico, determines the presence of a statistically significant trend in observed decrease in precipitation, and analyzes the relationship between precipitation conditions in the zone and the Ocean Niño Index. It is shown that there is a statistically significant trend of decreasing precipitation, and it is found that there is a correlation between the El Niño Oceanic Index and the conditions of extreme precipitation -humidity or drought- in the region.